2016
DOI: 10.1504/ijpqm.2016.075251
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors of Lean Six Sigma practices on business performance in Malaysia

Abstract: Less than 10% of companies worldwide benefited from Lean Six Sigma (LSS) projects despite huge investments, but do not yield promising tangible and intangible results. Prior researches on LSS implementation and business performance ignore to consider operational performance as mediator. This research examines the relationship of critical success factors of LSS practices on business performance, mediated by operational performance. The stratified sampling on 119 LSS practitioners in E&E sector, using smart PLS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Six Sigma was found to have a significant and positive impact on the organisational performance of the DPF. This result is consistent with that of past studies (Ahmed et al, 2018;Ali et al, 2016;Gunawan and Karimah, 2017;Hilton et al, 2008;Hwang et al, 2018;Jacobs et al, 2015;Mishra and Sharma, 2017;Nayeri and Rostami, 2016;Patyal and Koilakuntla, 2017;Sin et al, 2015;Singh et al, 2017;Swink and Jacobs, 2012;Uluskan et al, 2017;Zu et al, 2008). Results suggested that Six Sigma is critical for the DPF to achieve its goals and attain the planned performance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Six Sigma was found to have a significant and positive impact on the organisational performance of the DPF. This result is consistent with that of past studies (Ahmed et al, 2018;Ali et al, 2016;Gunawan and Karimah, 2017;Hilton et al, 2008;Hwang et al, 2018;Jacobs et al, 2015;Mishra and Sharma, 2017;Nayeri and Rostami, 2016;Patyal and Koilakuntla, 2017;Sin et al, 2015;Singh et al, 2017;Swink and Jacobs, 2012;Uluskan et al, 2017;Zu et al, 2008). Results suggested that Six Sigma is critical for the DPF to achieve its goals and attain the planned performance.…”
Section: Discussionsupporting
confidence: 91%
“…The bulk of evidence revealed that Six Sigma was positively and significantly related to organisational performance (Hilton et al, 2008;Zu et al, 2008;Swink and Jacobs, 2012;Jacobs et al, 2015;Sin et al, 2015;Ali et al, 2016;Nayeri and Rostami, 2016;Gunawan and Karimah, 2017;Hwang et al, 2018;Mishra and Sharma, 2017;Patyal and Koilakuntla, 2017;Singh et al, 2017;Uluskan et al, 2017;Ahmed et al, 2018). Six Sigma also has a role in enhancing quality management (Al-Aomar and Chaudhry, 2018;Raja et al, 2016), saving time and cost (Pande et al, 2000) and increasing innovation (He et al, 2015).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…There has been a noticeable increase in the popularity of LSS and its application in the industrial world (Yadav and Desai, 2016). The literature on the subject has also increased in recent years (Assarlind et al, 2012;Sreedharan and Raju, 2016;Yadav and Desai, 2016), and a range of empirical studies has been conducted (Ali et al, 2016;Habidin et al, 2016;Swarnakar and Vinodh, 2016). Nevertheless, although many case studies have investigated LSS implementation, it is still necessary to develop a deeper understanding of the application of LSS practices at the empirical level (Yadav and Desai, 2016), especially in the manufacturing sector (Albliwi et al (2015)).…”
Section: Introductionmentioning
confidence: 99%
“…LSS demands some substantial investment from an organization in creating various assets, generating resources, hardware and software purchase, preparation materials, consultation service, organization rewards and reorganizational system, MBB, BB and GB training, among others, to build and sustain the culture (Abu Bakar et al , 2015). The top management motivates the LSS implementation by allotment of financial rewards in the form of money or expensive goods and services or through investments in the areas such as cantina, wardrobes, salary increments or yearly bonuses (Abu Bakar et al , 2015; Ali et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“… (A) Antony et al (2018); (B) Ruben et al (2018); (C) Lande et al (2016); (D) Antony et al (2017); (E) Antony et al (2016); (F) Ali et al (2016); (G) Abu Bakar et al (2015); (H) Kumar et al (2015); (I) Antony (2014); (J) Lertwatta;napongchai and William Swierczek (2014); (K) Fadly Habidin and Mohd Yusof (2013); (L) Franchetti and Barnala (2013); (M) Antony et al (2012); (N) Hilton and Sohal (2012); (O) Laureani and Antony (2012); (P) Manville et al (2012); (Q) Psychogios and Tsironis (2012); (R) Psychogios et al (2012); (S) Jeyaraman and Kee Teo (2010); (T) Pepper and Spedding (2010); (U) Näslund (2008)…”
Section: Figurementioning
confidence: 99%